Biomechanical and Histologic Evaluation of LifeMesh™: A Novel Self-Fixating Mesh Adhesive. Issue 4 (April 2018) - Shahan, Charles P.; Stoikes, Nathaniel N.; Roan, Esra; Tatum, James; Webb, David L.; Voeller, Guy R.
Mesh fixation with the use of adhesives results in an immediate and total surface area adhesion of the mesh, removing the need for penetrating fixation points. The purpose of this study was to evaluate LifeMesh™, a prototype mesh adhesive technology which coats polypropylene mesh. The strength of the interface between mesh and tissue, inflammatory responses, and histology were measured at varying time points in a swine model, and these results were compared with sutures. Twenty Mongrel swine underwent implantation of LifeMesh™ and one piece of bare polypropylene mesh secured with suture (control). One additional piece of either LifeMesh™ or control was used for histopathologic evaluation. The implants were retrieved at 3, 7, and 14 days. Only 3- and 7-day specimens underwent lap shear testing. On Day 3, LifeMesh™ samples showed considerably less contraction than sutured samples. The interfacial strength of Day 3 LifeMesh™ samples was similar to that of sutured samples. At seven days, LifeMesh™ samples continued to show significantly less contraction than sutured samples. The strength of fixation at seven days was greater in the control samples. The histologic findings were similar in LifeMesh™ and control samples. LifeMesh™ showed significantly less contraction than sutured samples at all measured time points. Although fixation strength was similar at three days, the interfacial strength of LifeMesh™ remained unchanged, whereas sutured controls increased by day 7. With histologic equivalence, considerably less contraction, and similar early fixation strength, LifeMesh™ is a viable mesh fixation technology.